Firm-Created Word-of-Mouth Recommendation: Is it also worthwhile? - Maise Soares Pereira; Ivan Lapuente Garrido; Celso Augusto de Matos (BBR: Brazilian Business Review)
One of the fastest-growing marketing tactics used to persuade and win customers is management of recommendations through incentives to participants. However, these initiatives can raise questions, including ethical problems about credibility of the recommendation. With the aim of measuring the factors that influence acceptance of a wordof-mouth (WOM) recommendation, we propose a model able to relate and measure the impact of elements on acceptance of recommendations and the effect of participation in an organized WOM marketing program. We conducted a survey among 350 participants, using an instrument with a retrospective approach and presenting a hypothetical scenario. As results of the model, we highlight the expertise of the recommender and the similarity of this person with the receivers of the elements related with the recommendation message and their consequent willingness to accept it. We also identified that the existence of an incentive does not prevent acceptance of the recommendation, but it does reduce it, suggesting caution in use of this marketing tactic.